Lactobacillus fermentum F40-4 ameliorates hyperuricemia by modulating the gut microbiota and alleviating inflammation in mice. Issue 7 (17th March 2023) - Cao, Jiayuan; Wang, Ting; Liu, Yisuo; Zhou, Wei; Hao, Haining; Liu, Qiqi; Yin, Boxing; Yi, Huaxi
Abstract : L. fermentum F40-4 could inhibit UA synthetase activity in the liver to decrease UA production, promote expression level of UA excretion transporter NPT1 in the kidney and reshape microbiota in the gut to increase UA excretion, thereby alleviate HUA. Abstract : Hyperuricemia (HUA) is a systemic disease characterized by a disorder of purine metabolism and an abnormal increase in the serum level of uric acid (UA). Probiotics can exert potential therapeutic benefits against some metabolic diseases by regulating the intestinal microbiota. Lactobacillus fermentum F40-4 with UA-lowering activity of 87.40% was screened using purine as the target in vitro . The UA-lowering activity of L. fermentum F40-4 was further explored in a mouse model of HUA in vivo . L. fermentum F40-4 could downregulate serum levels of UA, blood urea nitrogen, creatinine, and xanthine oxidase by 40.84%, 11.61%, 57.66%, and 41.79%, respectively. L. fermentum F40-4 restored organ damage, and adjusted enzyme activity and transporter expression to promote the metabolic level of UA. In addition, L. fermentum F40-4 could reshape the gut microbiota and suppress inflammation to ameliorate HUA. An increment in intestinal UA excretion was documented. These findings suggest that L. fermentum F40-4 might serve as a potential probiotic for the prevention and treatment of HUA.